Postoperative bleeding complications in patients with hemophilia undergoing major orthopedic surgery: A prospective multicenter observational study. (8th February 2022) - Kleiboer, Brendan; Layer, Marcus A.; Cafuir, Lorraine A.; Cuker, Adam; Escobar, Miguel; Eyster, M. Elaine; Kraut, Eric; Leavitt, Andrew D.; Lentz, Steven R.; Quon, Doris; Ragni, Margaret V.; Thornhill, Dianne; et al.
Abstract: Background: Persons with hemophilia (PWH) are at risk for chronic hemophilic arthropathy (HA). Joint replacement surgery may be used to relieve intractable pain and/or restore joint function. Objectives: This multicenter, prospective, observational cohort study evaluated the rate of bleeding during the postoperative period after total hip (THA) or knee arthroplasty (TKA). Patients/Methods: We included PWH of any severity ≥18 years of age who were undergoing THA or TKA. Clinical decisions were made at the discretion of the treating physician according to local standards of care. Clinical data were prospectively recorded. Major bleeding was defined as bleeding in a critical site, bleeding that resulted in either a 2 g/dl or greater decrease in hemoglobin during any 24‐h period, or transfusion of two or more units of packed red blood cells. Results: One hundred thirty‐one procedures (98 TKA and 33 THA) were performed, 39 (29.8%) of which were complicated by major bleeding, including 46% of THA and 25% of TKA. The risk of major bleeding was increased in THA compared to TKA (OR 2.50, p = .05), and by the presence of an inhibitor (OR 4.29, p = .04), increased BMI (OR 4.49 and 6.09 for overweight and obese, respectively, compared to normal BMI, each p < .01), and non‐use of an antifibrinolytic medication (OR 3.00, p = .03). Neither continuous clotting factor infusion (versus bolus infusion) nor pharmacologic thromboprophylaxis were associated with bleeding risk. Conclusions: The bleeding risk remains substantial after THA and TKA in PWH, despite factor replacement. Use of antifibrinolytic medications is associated with decreased risk.